A encarnação como a suprema hierofania : releitura interpretativa do cristianismo - Silva, José Orlando da (2012)
The objective of this research is to analyze the concept of the incarnation of God, unfolding to a gradual creep in the design of phenomenology to the culmination at the conclusion of Mircea Eliade, when present incarnation as an integral factor of some religions and supreme hierophany. From this analysis, will be described the incarnation, passing through the Christian perspective of seeing it as truth and existential context of controversy to be safeguarded by the creeds of its major councils: Nicea and Chalcedon. Coming to the emergence of a new and modern reinterpretation that has the understanding of the incarnation as a metaphor , proposed by John Hick, based worldview of the religious pluralism; seeking discuss some consequences for the self-understanding of Christianity